Dynamic interaction of cBid with detergents, liposomes and mitochondria. - Stephanie Bleicken (Public Library of Science (PLoS), 2012)
The BH3-only protein Bid plays a key role in the induction of mitochondrial apoptosis, but its mechanism of action is still not completely understood. Here we studied the two main activation events of Bid: Caspase-8 cleavage and interaction with the membrane bilayer. We found a striking reversible behaviour of the dissociation-association events between the Bid fragments p15 and p7. Caspase-8 cleavage does not induce per se separation of the two Bid fragments, which remain in a stable complex resembling the full length Bid. Detergents trigger a complete dissociation, which can be fully reversed by detergent removal in a range of protein concentrations from 100 µM down to 500 nM. Incubation of cBid with cardiolipin-containing liposomes leads to partial dissociation of the complex. Only p15 (tBid) fragments are found at the membrane, while p7 shows no tendency to interact with the bilayer, but complete removal of p7 strongly increases the propensity of tBid to become membrane-associated. Despite the striking structural similarities of inactive Bid and Bax, Bid does not form oligomers and reacts differently in the presence of detergents and membranes, highlighting clear differences in the modes of action of the two proteins. The partial dissociation of cBid triggered by the membrane is suggested to depend on the strong and specific interaction between p15 and p7. The reversible disassembly and re-assembly of the cBid molecules at the membrane was as well proven by EPR using spin labeled cBid in the presence of isolated mitochondria. The observed dynamic dissociation of the two Bid fragments could allow the assistance to the pore-forming Bax to occur repeatedly and may explain the proposed "hit-and-run" mode of action of Bid at the bilayer.